The Influence of E-service Quality, E-trust and E-satisfaction Toward E-loyalty on Shopee Online Shopping Application Users - Rahmiati; Dani Octa Melani (Universitas Negeri Padang, 2021)
Abstract This study aims to analyze (1) the effect of e-service quality on e-satisfaction on Shopee users. (2) The effect of e-trust on e-satisfaction on Shopee users (3) The effect of e-service quality on e-loyalty on Shopee users in. (4) The effect of e-trust has an effect on e-loyalty of Shopee users. (5) The effect of e-satisfaction on e-loyalty on Shopee users. The population in this study were all Shopee users and the sample in this study were Shopee users who had shopped more than once. The sample size in this study was 217 respondents. Data was collected through the distribution of online questionnaires and data processing was carried out through SmartPLS software. The results of this study indicate that (1) E-service quality has a positive and significant effect on e-satisfaction on Shopee users. (2) E-trust has a positive and significant effect on e-satisfaction on Shopee users. (3) E-service quality has no positive and insignificant effect on e-loyalty of Shopee users. (4) E-loyalty has no negative and insignificant effect on e-loyalty on Shopee users. (5) E-satisfaction has a positive and significant effect on e-loyalty to Shopee users. and e-service quality and e-trust have a positive and significant effect on e-loyalty through e-satisfaction on Shopee users. Abstrak Penelitian ini bertujuan untuk menganalis (1) Pengaruh e-service quality terhadap e-satisfaction pada pengguna Shopee. (2) Pengaruh e-trust terhadap e-satisfaction pada pengguna Shopee (3) Pengaruh e-service quality terhadap e-loyalty pada pengguna Shopee di. (4) Pengaruh e-trust berpengaruh terhadap e-loyalty pada pengguna Shopee. (5) Pengaruh e-satisfaction terhadap e-loyalty pada pengguna Shopee. Populasi dalam penelitian ini adalah seluruh pengguna Shopee dan sampel pada penelitian ini adalah pengguna Shopee yang sudah berbelanja lebih dari satu kali. Jumlah sampel pada penelitian ini sebanyak 217 responden. Data dikumpulkan melalui penyebaran kuesioner secara online dan pengolahan data dilakukan melalui software SmartPLS. Hasil penelitian ini menunjukan bahwa (1) E-service quality berpengaruh secara positif dan signifikan terhadap e-satisfaction pada pengguna Shopee. (2) E-trust berpengaruh secara positif dan signifikan terhadap e-satisfaction pada pengguna Shopee. (3) E-service quality tidak berpengaruh secara positif dan tidak signifikan terhadap e-loyalty pada pengguna Shopee. (4) E-loyalty tidak berpengaruh secara negatif dan tidak signifikan terhadap e-loyalty pada pengguna Shopee. (5) E-satisfaction berpengaruh secara positif dan signifikan terhadap e-loyalty pada pengguna Shopee. serta e-service quality dan e-trust berpengaruh positif dan signifikan terhadap e-loyalty melalui e-satisfaction pada pengguna Shopee.